2012
DOI: 10.5740/jaoacint.cs2012_03
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Microplate-Based ORAC-Pyrogallol Red Assay for the Estimation of Antioxidant Capacity: First Action 2012.03

Abstract: A method was developed for microplate-based oxygen radicals absorbance capacity (ORAC) using pyrogallol red (PGR) as probe (ORAC-PGR). The method was evaluated for linearity, precision, and accuracy. In addition, the antioxidant capacity of commercial beverages, such as wines, fruit juices, and iced teas, was measured. Linearity of the area under the curve (AUC) versus Trolox concentration plots was [AUC = (845 +/- 110) + (23 +/- 2) [Trolox, microM]; R = 0.9961, n = 19]. Analyses showed better precision and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Automation indeed reduces analysis time and improves the efficiency of the assay in multiple analyses. Another method was developed for microplate-based ORAC using pyrogallol red (PGR) as probe with good linearity, precision, and accuracy . However, there are no published data on a manual ORAC assay.…”
Section: Hat-based Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Automation indeed reduces analysis time and improves the efficiency of the assay in multiple analyses. Another method was developed for microplate-based ORAC using pyrogallol red (PGR) as probe with good linearity, precision, and accuracy . However, there are no published data on a manual ORAC assay.…”
Section: Hat-based Methodsmentioning
confidence: 99%
“…Another method was developed for microplate-based ORAC using pyrogallol red (PGR) as probe with good linearity, precision, and accuracy. 26 However, there are no published data on a manual ORAC assay. The BIOOXYTECH AOP-490 microplate assay based on the reduction of Cu(II) to Cu(I) by the antioxidants in the oxygenated sample resulting in DNA cleavage was developed 27 and has not been directly compared to the original ORAC method.…”
Section: •−mentioning
confidence: 99%
“…Even though use of c-phycocyanin probe resulted in higher ORAC values than fluorescein in general, the relative ORAC values and trend among different samples were similar for both probes. Ortiz et al (2012) investigated the use of pyrogallol red probe for ORAC assay, which showed good linearity, precision and accuracy. Guclu, Kibrislioglu, Ozyurek, and Apak (2014) reported ORAC values of liver and kidney samples measured using p-aminobenzoic acid (PABA) as the fluorescent probe.…”
Section: Oxygen Radical Absorbance Capacity (Orac) Assaymentioning
confidence: 99%
“…Pyrogallol reacts faster than fluorescein with RCOO* radicals, and its consumption does not present induction times, even in the presence of very reactive oxidants, with the exception of ascorbic acid. First action ORAC assay has been reported both with fluorescein [226] (dextracts from tea, blueberry and grape skins) and pyrogallol red [228] (red wine, fruit juices and iced teas).…”
Section: Flavonoids -From Biosynthesis To Human Healthmentioning
confidence: 99%